Psychological Variables Explaining the Students’ Self-Perceived Well-Being in University, During the Pandemic - Bochiş, Laura Nicoleta; Barth, Karla Melinda; Florescu, Maria Cristina (Frontiers in Psychology, 2022)
Introduction: In the COVID-19 pandemic, Romanian universities switched to emergency relocation and online education, with students experiencing a sense of isolation, which affected their well-being, pace and normal learning style, relationships with other colleagues, and Professors. Beyond the technological obstacles that have arisen in learning, the aim of this study is to highlight the psychological variables that are associated and that explain the self-perceived well-being of students, in university, in the pandemic. The psychological variables studied were: the level of openness and personal autonomy, as personality traits of students but also the mechanisms for regulating their academic motivation. Method: We used a questionnaire-based survey; all four research instruments had been validated and adapted to the investigated population. The subjects were BA and MA students at the University of Oradea, Romania (N=150), the majority being females (95,5%) with the age range of 27 years old. Pearson Correlation and Multiple Linear Regression were used to test the two hypotheses. Results: Research data obtained in the correlation analysis, point out association relationships with moderate and high effects size, between positive attitude towards self, others and student life and: openness to learning, openness to aesthetics, behavioral autonomy, cognitive autonomy, intrinsic motivation and identification motivation. Furthermore, in regression analysis it was revealed that with regard to the variance of results concerning students' self-perceived well-being in university (positive attitude towards oneself, others and student life) it contributes both of students’ personality traits (such as openness and personal autonomy) and the intrinsic motivation and identification motivation. Conclusions. The fundamental conclusion of the research is that, although the personality traits of students explain in a higher percentage the variability of results in students' self-perceived well-being (in terms of positive attitude towards self, others and student life), motivation regulation mechanisms play an important role, especially in the conditions of online activities. The results have direct implications for the work carried out in universities. The educational policies developed by specialists and government will have to emphasize the ways of forming resilient student communities in periods of sudden transition and adaptation to change which take place in education and in society.